Association of low pregnancy-associated plasma protein A with the timing of delivery in babies with intrauterine growth restriction, babies showing suboptimal growth on serial scans, and well-grown babies - Fatima, Ayesha; Aich, Abhijit; Jamjute, Pradumna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The ideal timing for delivering babies with pre-eclampsia or small for gestational age is clear. There is agreement on delivering babies with pre-eclampsia and small for gestational age, but not for normally growing babies with low pregnancy-associated plasma protein A (PAPP-A). The study aimed to investigate the association of low PAPP-A with adverse pregnancy outcomes and ideal delivery timing in a well-grown baby with low PAPP-A as a risk factor. Methods: A retrospective study analyzed 3240 singleton pregnancies with first-trimester Down syndrome screening at local hospitals from January 2022 to April 2023. Among these, 130 singleton pregnancies had PAPP-A levels at the 5th centile, along with risk estimations and documentation. Results: In NCIC trust births, 3280 women were assessed for low PAPP-A. Of these, 130 had low PAPP-A levels. It revealed that 46.9% used Aspirin, with a high down screen risk found in 11.5%. In this study, 13.1% experienced pregnancy induced hypertension (PIH). 2 resulted in intrauterine fetal death (1.5%). 9 women (6.9%) experienced pre-term births. The study identified 8 newborns (6.25%) with birth weights below the 10th centile after >39+6 weeks, and 6 (4.6%) <3rd centile after 37+6 weeks. Conclusions: The study linked low PAPP-A to poor APGAR scores, stillbirth, growth issues, and special care unit admissions. Babies with low PAPP-A showed higher morbidity and mortality after 41 weeks. The findings indicate that delivery should occur between 40+0 and 40+6 weeks. Further research is needed to create an antenatal protocol for optimal delivery timing for babies with low PAPP-A.